Institutional distance and local isomorphism strategy - Salomon, Robert; Wu, Zheying (Journal of International Business Studies, 2012)
Firms face disadvantages when operating abroad. To overcome these disadvantages, foreign firms often adopt mitigating strategies. One such strategy is to imitate the practices of domestic firms (i.e., pursuing a strategy of local isomorphism). We understand little, however, about how firms vary in the extent of local isomorphism. To fill that gap, this paper explores the institutional drivers of local isomorphism decisions. The findings indicate that foreign firms choose a higher level of local isomorphism as the cultural, economic, and regulatory distances between the home country and the host country increase. Moreover, the evidence suggests that such local isomorphism is relatively enduring, as experience does not systematically moderate the relationship between distance and local isomorphism.